Complementary and alternative therapies usage among parents to children with cancer - Chong, Li Tsu; Norin John (TJPRC Pvt. Ltd., 2016)
The study is conducted at tertiary hospital at Sabah, Malaysia. A descriptive research design is used in this study to identify presence of any complementary and alternatives medicines (CAM) therapies usage amongst parents of paediatric oncology patients. A purposive sampling is used to recruit 30 samples of parents of the paediatric cancer patient with inclusion criteria that are families of patients who were more than 3 months past their date of diagnoses. Results showed 100% (n=30) of the parents all of them used it during conventional treatment. Majority 96.7% (n=29) used prayer as CAM therapies for their child,100% (n=30) of the parents use the therapies to relief their child’s symptoms,93.3% (n=28) have their own search for searching information regarding their choice of therapies. Majority (n=27, 90%) of the parents responded that the CAM therapies give effects in relief pain of their child even though all (100%) of the parents responded no effects in decreasing tumour size. This study has concluded that there is CAM therapies usage among parents to help relieves symptoms experienced by their children. However, the findings this study may has limitation in generalisation as due to small number of sample used in this study. Therefore it is only can be used as a primary data regarding the activity of using complementary and alternative therapies among the paediatric oncology patients.